Search for new phenomena in events with a photon and missing transverse momentum in pp collisions at √s =8 TeV with the ATLAS detector - Alconada Verzini, María Josefina (2015)
Results of a search for new phenomena in events with an energetic photon and large missing transverse momentum with the ATLAS experiment at the LHC are reported. Data were collected in proton-proton collisions at a center-of-mass energy of 8 TeV and correspond to an integrated luminosity of 20.3 fb-1. The observed data are well described by the expected Standard Model backgrounds. The expected (observed) upper limit on the fiducial cross section for the production of events with a photon and large missing transverse momentum is 6.1 (5.3) fb at 95% confidence level. Exclusion limits are presented on models of new phenomena with large extra spatial dimensions, supersymmetric quarks, and direct pair production of dark-matter candidates.